2007
DOI: 10.1016/j.bbabio.2007.03.006
|View full text |Cite
|
Sign up to set email alerts
|

A pathway for protons in nitric oxide reductase from Paracoccus denitrificans

Abstract: Nitric oxide reductase (NOR) from P. denitrificans is a membrane-bound protein complex that catalyses the reduction of NO to N(2)O (2NO+2e(-)+2H(+)-->N(2)O+H(2)O) as part of the denitrification process. Even though NO reduction is a highly exergonic reaction, and NOR belongs to the superfamily of O(2)-reducing, proton-pumping heme-copper oxidases (HCuOs), previous measurements have indicated that the reaction catalyzed by NOR is non-electrogenic, i.e. not contributing to the proton electrochemical gradient. Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
92
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(96 citation statements)
references
References 57 publications
4
92
0
Order By: Relevance
“…Bacterial NOR is a membrane-bound protein that catalyzes one step of this process, namely, the two-electron reduction of NO to N 2 O (17,19). With no crystal or solution structure available for bacterial NOR to date, sequence alignments and homology modeling (21,22) have indicated that NOR is structurally homologous to the largest subunit (subunit I) of hemecopper oxidases (HCOs) (23), enzymes that catalyze reduction of O 2 to water. The active sites of both NOR and HCO contain a proximal histidine-coordinated heme and a distal three histidine-coordinated metal center.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Bacterial NOR is a membrane-bound protein that catalyzes one step of this process, namely, the two-electron reduction of NO to N 2 O (17,19). With no crystal or solution structure available for bacterial NOR to date, sequence alignments and homology modeling (21,22) have indicated that NOR is structurally homologous to the largest subunit (subunit I) of hemecopper oxidases (HCOs) (23), enzymes that catalyze reduction of O 2 to water. The active sites of both NOR and HCO contain a proximal histidine-coordinated heme and a distal three histidine-coordinated metal center.…”
mentioning
confidence: 99%
“…However, the metal center in HCOs is occupied by a copper (called Cu B ), whereas a nonheme iron is present in NOR (called Fe B ) (23,24). In addition, two conserved glutamates, shown by modeling to be close to the Fe B site (21,22), are found to be essential for NOR activity (24,25). Some members of HCOs such as cytochrome cbb 3 oxidase display NOR activity (26)(27)(28), although the activity is ∼50-fold lower than native NOR (26).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Contrary to COXs, the proton transfer pathway in NOR was less established, but biochemical and biophysical studies unambiguously showed no proton pumping activity and the catalytic proton transfer from the outside of the membrane in cNOR (11,12). The structure of P. aeruginosa cNOR demonstrated that there is no proton transfer pathway from the inside of the membrane and suggested two possible proton transfer pathways, channels 1 and 2, from the outside of the membrane (13) (Fig.…”
Section: Proton Transfer From Outside Versus Inside Of Cellular Membranementioning
confidence: 98%
“…NORs and some COXs have crossreactivity with respective substrate (8)(9)(10), further supporting the view that NOR is evolutionary related to COX. However, NOR shows no proton pumping activity (11,12), whereas COX can generate the proton gradient by pumping protons in a process coupled with O 2 reduction. The produced proton gradient is essential for efficient ATP synthesis.…”
Section: Introductionmentioning
confidence: 99%